No humdrum life - Rudra, Kalyan (New Delhi, 2004)
The book vividly describes how an IPS officer traverses the Various stages of his career, starting from training, holding charge of districts, stints of Central deputation and ending up as the head of the State Police organization.
Keywords: Police administration